Influence of Chemoautotrophic Organic Carbon on Sediment and Its Infauna in the Vicinity of the Rainbow Vent Field - Roohi, Reyhaneh; Hoogenboom, Ragna; Van Bommel, Ronald; Van Der Meer, Marcel T. J.; Mienis, Furu; Gollner, Sabine (Frontiers in Marine Science, 2022)
Hydrothermal vents have been recognised as isolated islands of productivity in the deep sea, but very little is known about the transport and export of chemoautotrophic produced organic carbon to vent surrounding habitats. Here, we investigate vent carbon export and its influence on benthic food webs in sediments at the Rainbow (RB) vent field at the Mid Atlantic Ridge in 2200 m water depth. Two sites were considered along the dispersal direction of the RB vent plume for sample collection: the close vicinity at about 30-100 m (“near-vent”); and at 4 km distance (“off-vent”) to the nearest venting area. At both sites, box corers were used to sample sediments and their fauna. A turbidity sensor mounted on a CTD/Rosette provided data on the presence of a vent fluid plume in the water column. Niskin bottles were used to sample suspended particulate organic matter (SPOM) from the plume, as well as from surface waters at 75 m depth. SPOM, sediments and fauna were analysed for nitrogen and carbon stable isotopes. Carbon derived from in situ chemoautotrophy, characterised by depleted δ13C, was taken up by infauna close to the venting area as the main nutrition source, while fauna at the off-vent site showed less depleted δ13C with a signature more typical for photosynthetic- derived material. Nematodes were the most abundant faunal taxon. Their abundance and biomass were variable and not different at the two studied sites. In situ derived organic matter was traced back in the food web in the close vicinity of the venting area. The connectivity of vent and non-vent habitats should be taken appropriately into account when designing future spatial management plans with regard to deep-seabed mining at hydrothermal vents.